Differential regulation of STP, LTP and LTD by structurally diverse NMDA receptor subunit-specific positive allosteric modulators. (1st January 2022) - France, G.; Volianskis, R.; Ingram, R.; Bannister, N.; Rothärmel, R.; Irvine, M.W.; Fang, G.; Burnell, E.S.; Sapkota, K.; Costa, B.M.; Chopra, D.A.; Dravid, S.M.; et al.
Abstract: Different types of memory are thought to rely on different types of synaptic plasticity, many of which depend on the activation of the N-Methyl-D Aspartate (NMDA) subtype of glutamate receptors. Accordingly, there is considerable interest in the possibility of using positive allosteric modulators (PAMs) of NMDA receptors (NMDARs) as cognitive enhancers. Here we firstly review the evidence that NMDA receptor-dependent forms of synaptic plasticity: short-term potentiation (STP), long-term potentiation (LTP) and long-term depression (LTD) can be pharmacologically differentiated by using NMDAR ligands. These observations suggest that PAMs of NMDAR function, depending on their subtype selectivity, might differentially regulate STP, LTP and LTD. To test this hypothesis, we secondly performed experiments in rodent hippocampal slices with UBP714 (a GluN2A/2B preferring PAM), CIQ (a GluN2C/D selective PAM) and UBP709 (a pan-PAM that potentiates all GluN2 subunits). We report here, for the first time, that: (i) UBP714 potentiates sub-maximal LTP and reduces LTD; (ii) CIQ potentiates STP without affecting LTP; (iii) UBP709 enhances LTD and decreases LTP. We conclude that PAMs can differentially regulate distinct forms of NMDAR-dependent synaptic plasticity due to their subtype selectivity. This article is part of the Neuropharmacology Special Issue on 'Glutamate Receptors – NMDA receptors'. Highlights: NMDAR-dependent STP, LTP and LTD can be dissociated pharmacologically GluN2A/2B PAM UBP714 potentiates LTP and reduces LTD GluN2C/D PAM CIQ potentiates STP without affecting LTP NMDAR pan-PAM UBP709 potentiates LTD and reduces LTP